PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP MINAT BELI ULANG KONSUMEN (STUDI PADA PORTOBELLO CAFÉ SEMARANG ) - Rendhy Yosua Putra Sinambela; Agus Hermani DS (Universitas Diponegoro, 2019)
The development of the culinary service business is increasing rapidly at this time, they compete in providing the best service to retain their customers. This research was conducted at Portobello Café Semarang. Portobello Café Semarang sales data shows fluctuations in the number of sales and the number of complaints from Portobello Cafe service users regarding services and prices. Portobello Café must be able to provide good service to its customers, good service must be balanced with the price according to what is provided by Portobello Café Semarang. This study aims to determine the effect of service quality (X1) and price (X2) on consumer repurchase (Y) interest in Portobello Café Semarang. This type of research uses explanatory research with a quantitative approach. Methods of data collection using a preliminary interview, data collection using a questionnaire with a sample of 100 respondents with convenience sampling techniques. The results of the study show that partially the service quality and price variables influence the repurchase intention positively and significantly. Regression coefficient value on service quality variable (0.677) and price (0.493). The value of work service quality variables (4,706) and price (4,902). Service quality and price simultaneously influence the repurchase intention variable positively and significantly with multiple regression coefficient values. The multiple regression coefficient value of the service quality variable (0.497) and price (0.374) with the calculated value (19,305). Suggestions that can be conveyed to the company are to increase the consumer's buying interest related to the interest in having the main preference on the product and the interest to always look for information about the product. Improving the quality of service of Portobello Café, especially on the ability of employees to recognize consumers as customers and understand every customer need. Conduct appropriate policies relating to pricing, namely by conducting price comparisons with other equivalent cafes.